Public policy of partnerships government and business: EU experience for Ukraine - Vnuchko, Svitlana; Teremko, Viktor; Perepelytsia, Nataliia; Shtelmashenko, Anastasiia; Kolotylo, Volodymyr; Turenko, Vitalii (Edelweiss Applied Science and Technology, 2024)
The article defines the forms of interaction between government and business within the framework of EU public policy and finds out Ukraine's readiness to be included in this process. The authors note that the interaction between business and government in the EU occurs both at the supranational level (European Commission, European Parliament, Council of Ministers, European Social and Economic Committee) and national structures (national governments, national parliaments). Openness, participation, accountability, efficiency, and coherence are the main principles of EU good governance, which are the basis of interaction. The authors come to the conclusion that Ukrainian business associations actively cooperate with the EU business environment: EESC, BusinessEurope, Eurochambers, SMEunited, etc. However, it is still too early to talk about the completion of the formation of an effective institutional system in Ukraine capable of ensuring effective interaction between the government and business based on clearly established rules and norms of their self-regulation, which would correspond to all five principles of good governance of the EU.